Clinical and preclinical translation of cell-based therapies using adipose tissue-derived cells - Gimble, Jeffrey M (BioMed Central, 2010)
Adipose tissue is now recognized as an accessible, abundant, and reliable site for the isolation of adult stem cells suitable for tissue engineering and regenerative medicine applications. The past decade has witnessed an explosion of preclinical data relating to the isolation, characterization, cryopreservation, differentiation, and transplantation of freshly isolated stromal vascular fraction cells and adherent, culture-expanded, adipose-derived stromal/stem cells in vitro and in animal models. This body of work has provided evidence supporting clinical translational applications of adipose-derived cells in safety and efficacy trials. The present article reviews the case reports and phase I-III clinical evidence using autologous adipose-derived cells that have been published, to date, in the fields of gastroenterology, neurology, orthopedics, reconstructive surgery, and related clinical disciplines. Future directions and challenges facing the field are discussed and evaluated.